Concurrent optogenetic motor mapping of multiple limbs in awake mice reveals cortical organization of coordinated movements - Nischal Khanal; Jonah A. Padawer-Curry; Trevor Voss; Kevin A. Schulte; Annie R. Bice; Adam Q. Bauer (Brain Stimulation, 2024)
Background: Motor mapping allows for determining the macroscopic organization of motor circuits and corresponding motor movement representations on the cortex. Techniques such as intracortical microstimulation (ICMS) are robust, but can be time consuming and invasive, making them non-ideal for cortex-wide mapping or longitudinal studies. In contrast, optogenetic motor mapping offers a rapid and minimally invasive technique, enabling mapping with high spatiotemporal resolution. However, motor mapping has seen limited use in tracking 3-dimensonal, multi-limb movements in awake animals. This gap has left open questions regarding the underlying organizational principles of motor control of coordinated, ethologically-relevant movements involving multiple limbs. Objective: Our first objective was to develop Multi-limb Optogenetic Motor Mapping (MOMM) to concurrently map motor movement representations of multiple limbs with high fidelity in awake mice. Having established MOMM, our next objective was determine whether maps of coordinated and ethologically-relevant motor output were topographically organized on the cortex. Methods: We combine optogenetic stimulation with a deep learning driven pose-estimation toolbox, DeepLabCut (DLC), and 3-dimensional triangulation to concurrently map motor movements of multiple limbs in awake mice. Results: MOMM consistently revealed cortical topographies for all mapped features within and across mice. Many motor maps overlapped and were topographically similar. Several motor movement representations extended beyond cytoarchitecturally defined somatomotor cortex. Finer articulations of the forepaw resided within gross motor movement representations of the forelimb. Moreover, many cortical sites exhibited concurrent limb coactivation when photostimulated, prompting the identification of several cortical regions harboring coordinated and ethologically-relevant movements. Conclusions: The cortex appears to be topographically organized by motor programs, which are responsible for coordinated, multi-limbed, and behavior-like movements.